Wholesale produce auctions and regional food systems: The case of Seneca produce auction. Issue 3 (26th March 2018) - Reid, Judson; Simmonds, Derek; Newbold, Elizabeth
Abstract: Produce auctions are local aggregation points that facilitate access for small-scale fruit, flower and vegetable farmers to wholesale buyers from a broader geography. Buyers purchase lots from multiple farmers to fulfill wholesale demand and then retail the product to the consumers. Sales are held multiple times per week to create a consistent supply for buyers and a regular market for the farmers. With over 70 produce auctions located in eastern North America, this is a growing trend of intermediated markets. Currently, there are six active produce auctions in New York State, with two more in planning stages. Produce auctions have a positive economic impact on the communities in which they are located, as well as on those who sell and/or buy at the auction. Community values inherent to these populations contribute to the success of produce auctions as an intermediated market. As the auction market channel continues to grow, buyer and consumer education on the benefits of local auctions is important. As these auctions are based in horse-and-buggy communities, extension education needs to be tailored to Amish and Mennonite populations. Auction houses, as well as farmers, will need to stay current with federal food safety regulations and market-based requirements to remain competitive.